The effect of input-based tasks on grammar acquisition among beginner-level English language learners - Majeed Noroozi; Seyyedmohammad Taheri (Universitas Syiah Kuala, 2026)
This study examines the efficacy of input-based tasks within the framework of Task-Based Language Teaching (TBLT) and the Presentation-Practice-Production (PPP) methods in assisting beginner-level English learners in acquiring and retaining the grammatical feature of the plural -s. A total of 45 Iranian English language learners were randomly assigned to three groups: the TBLT group, the PPP group, and the control group. A quasi-experimental research design was employed to assess participants’ comprehension and production abilities through the administration of pretest, posttest 1, and posttest 2. The data were analyzed using two-way repeated measures ANOVA along with Tukey post-hoc comparison tests. The results of the study indicate significant improvements in performance for both the TBLT and PPP groups when compared to the control group, with more notable gains observed in input-based tasks (p < 0.05). Although the TBLT group outperformed the PPP group in terms of plural -s comprehension and same-or-different tasks during both posttests, the differences were not found to be statistically significant at posttest 2 (p > 0.05). Both experimental groups exhibited a decline in performance at posttest 2; however, the TBLT group still maintained comparatively higher overall scores. These findings emphasize the pedagogical benefits of TBLT’s contextualized and meaningful input in fostering long-term grammatical learning and retention, while PPP showed stronger short-term effects but struggled with sustained retention. The study highlights the pedagogical potential of input-based tasks in grammar instruction, particularly for beginner-level learners in English language classrooms.